Competing pathways in odd oxygen photochemistry of the martian atmosphere. (February 2020) - Modak, Ashimananda; Sheel, Varun; Lefèvre, Franck
Abstract: Though the photochemistry of Mars is comparatively simple, the orbital properties of Mars and its exposure to solar influx lead to pronounced seasonal and latitudinal variations of short lived species (trace gases). We have a fair understanding of such species, such as ozone, that determine the equilibrium state of the Martian atmosphere. However, in previous studies a quantitative comparison between various production and loss processes, with their relative importance in determining the abundance of trace species, has not been performed. Here we use the photochemistry coupled LMD GCM to study in detail the important source and sink processes of odd oxygen (ozone and oxygen atoms) and their contribution in different locations and seasons. This becomes especially important due to the high seasonal variability of water vapor involved in the photochemistry. The study shows few interesting features about the processes. The loss due to OH peaks above 50 km irrespective of season but the peak value increases during perihelion season due to increased availability of water vapor in the heights. Contrary to expectations, the day time loss rates due to HO2, which is the most significant loss of odd oxygen do not show a strong seasonal variation. Ox is in photochemical equilibrium up to about 30 km in the aphelion season and up to 45 km in the perihelion season. In the photochemical equilibrium domain, HO2 +O is the dominant loss process of Ox, while above this domain, the HOx ​+ ​O, H ​+ ​O3 and O ​+ ​O reactions have comparable contributions to the Ox loss. The O ​+ ​O3 reaction is always a minor contribution to the Ox loss. Highlights: We study seasonal and spatial variability of the relative contributions of source/sink processes of Ox in Martian atmosphere. Loss rate of odd oxygen peaks in the region 45–60 km, with OH contributing 30–45% of the total loss. In the photochemical equilibrium domain, HO2 +O is the dominant loss process of Ox, and above this domain, losses with HOx, H, and O are comparable.